2008
DOI: 10.1002/jsfa.3265
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐ or post‐harvest applications of putrescine and low temperature storage affect fruit ripening and quality of ‘Angelino’ plum

Abstract: BACKGROUND: Plum has a very short storage life. The role of pre-or post-harvest applications of putrescine (PUT) and low temperature storage on fruit ripening and quality was investigated in plum fruit (Prunus salicina Lindl. cv. Angelino).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
40
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 42 publications
11
40
0
Order By: Relevance
“…However, bell pepper coated with 12% gum arabic exhibited a lower increase in sugar content, which may be described due to its ability to slow down the conversion of starch into sugars. Similar observations were also reported by Khan et al [58] where putrescine treatment delayed the ripening process and maintained lower sugar levels in peach fruit.…”
Section: Discussionsupporting
confidence: 90%
“…However, bell pepper coated with 12% gum arabic exhibited a lower increase in sugar content, which may be described due to its ability to slow down the conversion of starch into sugars. Similar observations were also reported by Khan et al [58] where putrescine treatment delayed the ripening process and maintained lower sugar levels in peach fruit.…”
Section: Discussionsupporting
confidence: 90%
“…The highest TSS content in the trials was determined in the control application at the end of storage (14.3%), while the lowest TSS values were determined in the Put treatment (10.7%) on the 7 th day. These results are in accordance with the finding by Khan et al (2008), Bal (2012), who reported that Put-treated fruit stored at low temperatures exhibited lower soluble solid content than untreated fruits.…”
Section: Total Soluble Solidssupporting
confidence: 93%
“…Exogenously applied Put reduced fruit deterioration and increaseed shelf life of lemon (Citrus limon [L.] Burm. f., Martínez-Romero et al, 1999), apricot (Prunus armeniaca L., Martínez-Romero et al, 2002), sweet cherry (Prunus avium [L.] L., Bal, 2012), strawberry (Fragaria ×ananassa Duchesne ex Rozier, Khosroshahi et al, 2007), and plum (Prunus salicina Lindl., Perez-Vicente et al, 2002;Khan et al, 2008). Plums treated with 1 mM Put showed delayed and reduced ethylene production together with higher fruit firmness, lower soluble solutions and titratable acids, reduced weight loss, and delayed color change, which led to extended storage life Serrano et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…6). Khan et al (2008) also reported that the treated plum fruits (cv. 'Angelino') with putrescine had the lowest amount of maturity index during storage.…”
Section: Maturity Indexmentioning
confidence: 92%
“…Little research has been done on improving the quality properties and shelf life of plum fruit. Recent works studied low temperature storage and application of putrescine (Khan et al 2008), postharvest treatments whit polyamines , calcium and heat (Serrano et al 2004), 1-methylcyclopropene (1-MCP) (Menniti et al 2006) and salicylic acid (Luo et al 2011).…”
Section: Introductionmentioning
confidence: 99%